Characterization, biological control of Chrysoporthe cubensis and Chrysoporthe deuterocubensis and fungal diversity in Eucalyptus plantations in Malaysia - Awing, Norida Hanim (2023)
Eucalyptus spp. trees are essential in Malaysia's forest plantation sector due to their fast growth rate, high wood density, and higher economic return. These characteristics make them a valuable source of alternative wood for paper manufacture and construction materials. Long-term plantations with short rotations, extreme human disturbance, and natural allelochemical activities from Eucalyptus tissues may reduce the native microbiome diversity in Eucalyptus hybrid (Eucalyptus urophylla x Eucalyptus grandis) plantations. As part of exploring the diversity of fungal groups that exist in the soil and on the leaves of Eucalyptus, the study also assesses the Chrysoporthe stem canker disease affecting Eucalyptus plantations from four regions in Malaysia: Kelantan, Pahang, Sabah, and Selangor. The discovery of these canker diseases led to further action in developing biocontrol agents to eliminate and control the disease. Therefore, these present studies aim to; i) utilise a metagenomic approach to fungal communities in soil and on the leaves of Eucalyptus spp., ii) assess the pathogenicity of the fungi causing stem canker disease, and iii) evaluate biocontrol agents of the secondary metabolite from antagonism activity against Chrysoporthe stem canker disease. To perform the study, a total of 6 phyla, 32 classes, and 821 genera of fungi were discovered from two different types of samples: soil and leaves in the Eucalyptus plantation by shotgun metagenomic sequencing. According to the Chao1 estimator and the Shannon index, fungal species diversity and richness are lower in leaves than in soil samples. The fungi species from classes of Fusarium, Humicola, Talaromyces, and Trichoderma were discovered as potential biological controls in two different samples from four different regions. The results will help to better understand fungal interactions and provide information on Eucalyptus hybrid (Eucalyptus urophylla x Eucalyptus grandis) fungal communities, particularly the role of pathogenic fungi, which can be useful in minimising disease-related fungal communities. To reveal the study on the assessment of Chrysoporthe stem canker disease, the molecular DNA sequence data of the ITS, β-tubulin 2, and TEF-1α with additional mating type genes MAT1-1 and MAT1-2, pheromone genes (ppg1, ppg2, pre1, and pre2) and pathogenicity studies in field trials confirmed the stem canker disease caused by Chrysoporthe cubensis and Chrysoporthe deuterocubensis. Both Chrysoporthe cubensis and Chrysoporthe deuterocubensis gave rise to lesions on the wounded (2.9 – 6.9 cm) and were equally pathogenic to Eucalyptus hybrid and Eucalyptus pellita. This finding should be regarded as a biosecurity concern in Malaysia's forest plantation industry. Hence, further studies were developed on Eucalyptus endophyte fungi for potential sources of biological compounds for producing secondary metabolite products. Of the 88 selected endophyte isolates, only six isolates positive against the Chrysoporthe culture were processed to produce crude compounds. The 27 major compounds are present in most potential isolates from the Botryosphaeria dothidea strain and may be the reasons this endophyte can go against Chrysoporthe spp. with 82.14-78.57% inhibition rates. It includes an α-pyridone derivative, 3-hydroxy-2-methoxy-5- methylpyridin-2(1H)-one, and 3-hydroxy-N-(1-hydroxy-4-methylpentan-2-yl)-5- oxohexanamide. The extract displayed was believed to have potent antifungal and antimicrobial activity with the same mechanism as carbendazim (a nationally licensed fungicide). To conclude, the study reveals that Eucalyptus plantations in Malaysia have been identified and confirmed. While the biological compound identified from endophytic fungi can be utilised for commercialization in controlling the Eucalyptus Chrysoporthe stem canker disease outbreak in the plantation in Malaysia.